Effects of the long-term administration of alendronate on the mechanical properties of the basal bone and on osseointegration - Verzola, Mario Henrique A. [UNESP]; Frizzera, Fausto [UNESP]; de Oliveira, Guilherme J.P.L. [UNESP]; Pereira, Rosa M. R.; Rodrigues-Filho, Ubirajara P.; Nonaka, Keico Okino; Orrico, Silvana R.P. [UNESP] (Wiley, 2015)
To evaluate the effect of the long-term administration of alendronate on the mechanical properties of the basal bone and on osseointegration. Material and methods: One hundred and sixty female rats were randomly allocated into two equally sized groups: the control (CTL) group, which received the subcutaneous administration of saline solution, and the alendronate (ALD) group, which received the subcutaneous administration of alendronate (1 mg/kg/week). After 120 days of these therapies, one implant was placed in each rat tibia. Ten animals in each group were euthanized at 5, 10, 15, 20, 25, 30, 45, or 60 days after surgery. The tibias with implants evaluated regarding the removal torque, bone-implant contact (BIC), the bone area fraction occupancy (BAFO), and Ca/P ratio. The femurs were evaluated regarding bone mineral density (BMD) and using mechanical tests to evaluate the maximal force of fracture, stiffness, and tenacity. Results: The ALD group presented statistically significant higher BMD (all periods except 15 days), maximal force of fracture (at 20, 30, and 45 days), tenacity (at 10, 20, 30, and 45 days), stiffness (45 days), removal torque (at 20, 25 and 30 days), BIC (at 20 and 60 days), and BAFO (at 20, 30, and 45 days) than the CTL group. No differences were found between the groups regarding the Ca/P ratio. Conclusion: Previous long-term therapy with alendronate caused an increase in the BMD, maximal force of fracture of the bone without changing the inorganic composition and elastic deformability of this tissue. Furthermore, the ALD therapy enhanced osseointegration. Copyright © 2015 John Wiley
Keywords: Alendronate; Bone density; Bone remodeling; Mechanical tests; Osseointegration